A trajectory tracking genetic fuzzy logic controller for nuclear research reactors - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this study, a trajectory tracking genetic fuzzy logic controller was designed for research reactors. Membership functions and action weights of the fuzzy controller were optimally determined by genetic algorithms. The behavior of the controller was tested for various initial and desired power levels as well as under disturbance. It was seen that the controller could control the system successfully under all conditions within the acceptable error tolerance. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Nuclear reactor control; Fuzzy logic controller; Genetic algorithms; IDENTIFICATION